Modern Management of Clinical Chorioamnionitis - Thomas Westover; Robert A. Knuppel (Hindawi Limited, 1995)
Clinical chorioamnionitis continues to contribute to fetal and maternal morbidity and mortality. Significant advances have been made in the last 20 years in understanding the pathophysiologic processes leading to chorioamnionitis. This review addresses the history, incidence, pathophysiology, host defenses, risk factors, diagnosis, and maternal and neonatal management of clinically evident chorioamnionitis. After a detailed review of the physiologic processes leading to clinical chorioamnionitis and sepsis, we present a modern management scheme designed to optimize perinatal outcome for both mother and fetus.